Big and small - Godfrey, Rachel; Pitts, Sorrel (UK Ladybird Books, 2019)
Some animals are big, and some are small. Some animals live in hot places, and some live in dry places. All animals are different!
Inspired by BBC Earth TV series and developed with input from BBC Earth natural history specialists
Science (Animals)
Keywords: Animals